2013
DOI: 10.1016/j.joca.2013.04.003
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 receptor antagonist gene as a predictive biomarker of progression of knee osteoarthritis in a population cohort

Abstract: Objective Within the interleukin-1 (IL-1) cytokine family, IL-1 receptor antagonist (IL1RN) gene variants have been associated with radiological severity of knee osteoarthritis (OA) in cross-sectional studies. The present study tested the relation between IL1RN gene variants and progression of knee OA assessed radiographically by change in Kellgren-Lawrence (KL) score over time. Design 1153 Caucasian adults (age range 44-89) from the Johnson County Osteoarthritis Project were evaluated for unequivocal radiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
39
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 45 publications
1
39
1
1
Order By: Relevance
“…Examining common variants of the IL1RN gene revealed that the rs4251961 minor allele is associated with a lowered serum level of IL-1RN and that the rs579543 single nucleotide polymorphism (SNP) is also independently associated with IL-1RN levels, whereas the IL1RN 1018 haplotype correlates with higher concentrations of IL-1β and IFNγ 22 . These findings have been confirmed in three independent cohorts 26 , and further research has demonstrated that these factors affect the pathophysiology of human infections 27 and the risk of developing insulin resistance 28 and knee osteoarthritis 29 .…”
Section: Risk Factors and Causes Of Inflammageingmentioning
confidence: 61%
“…Examining common variants of the IL1RN gene revealed that the rs4251961 minor allele is associated with a lowered serum level of IL-1RN and that the rs579543 single nucleotide polymorphism (SNP) is also independently associated with IL-1RN levels, whereas the IL1RN 1018 haplotype correlates with higher concentrations of IL-1β and IFNγ 22 . These findings have been confirmed in three independent cohorts 26 , and further research has demonstrated that these factors affect the pathophysiology of human infections 27 and the risk of developing insulin resistance 28 and knee osteoarthritis 29 .…”
Section: Risk Factors and Causes Of Inflammageingmentioning
confidence: 61%
“…Thus, IL1RN gene markers could be useful in monitoring patients for medical management and possibly drug development. 4 Analysis of SNPs in the IL1R1 gene revealed an association with severe hand OA in family-based and case-control studies, with the strongest candidate for predisposition to disease being the SNP rs2287047. 5 Some IL1 gene cluster polymorphisms seem to affect risk of small joint OA as well.…”
Section: Asthma Osteoarthritis Autoimmune Diseasesmentioning
confidence: 99%
“…IL-1 and TNF-α are the two most important pro-inflammatory factors during cartilage matrix degradation and articular cartilage damage in OA pathology, and thus are natural targets for therapy in OA (20,34). IL-1 may elevate matrix metalloproteinase expression in chondrocytes and synoviocytes and promote prostaglandin E production, and it also inhibits the synthesis of hyaline cartilage specific II, IX collagen and protein polysaccharide, acting synergistically with TNF-α (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…TGF-β1) are significantly decreased, while inflammatory cytokine expression (e.g. IL-1) increases (20,21). As such, blocking the adverse effects of IL-1 signalling in OA could potentially inhibit cartilage matrix degradation and IL-1Ra could play a major protective role in this process (22).…”
mentioning
confidence: 99%